BORDER COMMUNITY CHALLENGES IN WARTIME UKRAINE: ADVANCING SOCIAL CHANGE AND SOCIAL WELFARE THROUGH SERVICE LEARNING - Verbytska, Anna (Current Problems of Sustainable Development, 2026)
The article examines the key challenges facing border territorial communities of Chernihiv oblast under conditions of full-scale war. The findings of the analysis provide the empirical and conceptual foundation for the development and implementation of a Service Learning model as a tool for advancing social change and strengthening social welfare at the community level. The empirical base of the study comprises the results of focus group interviews and semi-structured in-depth interviews conducted with 120 representatives of four key stakeholder groups: local self-government bodies, the civil society sector, the private sector, and educational institutions across five communities of the region: Chernihiv, Horodnia, Nizhyn, Pryluky, and Koriukivka. The sample was formed on the basis of an intersectoral approach, ensuring representation of actors involved in the formation, implementation, and expert support of socio-economic and governance processes at the local level. The study identifies six systemic challenges that define the development trajectory of the investigated communities. First, security instability and critical infrastructure constraints (particularly acute in border communities) structurally limit investment attraction, long-term planning, and institutional functioning. Second, demographic decline and loss of human capital, manifested through youth outmigration, declining birth rates, labour emigration, and accelerating population ageing, undermine the reproductive capacity of local labour markets and educational systems. Third, structural labour shortages and transformation of local labour markets reflect a deep mismatch between the educational system and the actual demands of the local economy, compounded by mobilisation-driven workforce reduction. Fourth, economic instability and financial dependence of communities on external grants and international support significantly narrow the space for independent development strategies. Fifth, psychosocial vulnerability of the population, expressed through the accumulation of chronic emotional exhaustion, burnout among civil society activists, and growing demand for psychological support, is gradually becoming an independent factor of social fragility. Sixth, institutional fragmentation and weak intersectoral interaction remain pervasive across all studied communities, with partnership between key actors remaining largely situational rather than institutionalised. It is defined that the intensity and configuration of these challenges vary significantly depending on the territorial location and institutional capacity of each community. Border communities demonstrate the highest levels of security vulnerability and economic dependence, while larger city communities face institutional fragmentation and workforce deficits. The study suggests that a comprehensive understanding of the identified challenges provides the foundation for the purposeful application of Service Learning methodology as an educational instrument capable of strengthening intersectoral linkages, developing practical competencies among youth, engaging universities as platforms for community partnership, and fostering sustainable community recovery.